2005
DOI: 10.1088/0963-0252/14/3/025
|View full text |Cite
|
Sign up to set email alerts
|

New chamber walls conditioning and cleaning strategies to improve the stability of plasma processes

Abstract: One major challenge in plasma etching processes for integrated circuit fabrication is to achieve a good wafer-to-wafer repeatability. This requires a perfect control of the plasma chamber wall conditions. For silicon etching processes, which deposit SiO y Cl z layers on the chamber walls, this is achieved by cleaning the interior surfaces of the plasma chamber with an SF 6 -based plasma after each wafer is etched. However, x-ray photoelectron spectroscopy analysis of the reactor wall surfaces shows that the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 21 publications
1
71
0
1
Order By: Relevance
“…23 In the early 2000s, conditioning chamber walls with in situ wall deposition significantly improved wafer-to-wafer repeatability. 24 However, a significant portion of process control still relies on compensation to correct for systematic nonuniformities that are amplified by the coupled transport of ions and neutrals to the wafer surface during continuous processing. Despite widespread usage of balancing competing behaviors, compensation adds cost and complexity to the system, thereby providing a smaller process window.…”
Section: Limitations Of Continuous Etchingmentioning
confidence: 99%
“…23 In the early 2000s, conditioning chamber walls with in situ wall deposition significantly improved wafer-to-wafer repeatability. 24 However, a significant portion of process control still relies on compensation to correct for systematic nonuniformities that are amplified by the coupled transport of ions and neutrals to the wafer surface during continuous processing. Despite widespread usage of balancing competing behaviors, compensation adds cost and complexity to the system, thereby providing a smaller process window.…”
Section: Limitations Of Continuous Etchingmentioning
confidence: 99%
“…In recent papers 5,8 we have presented a technique, which allows us to measure by XPS the chemical nature and thickness of the layers deposited on the reactor walls after an etching process. As shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The empirical approach used in the industry has shown that the most effective way to maintain stable plasma processing conditions together with a high mean time between chamber ͑MTBC͒ wet cleans is to clean up the reactor walls after each wafer is etched. 7,8 However, it remains difficult to perfectly remove the coatings from all the parts of the chamber 9 because their chemical nature is unknown ab initio and may greatly vary depending on the processing conditions, on the photoresist coverage of the wafer, and on the material being etched. 5 It is thus important to analyze the chemical nature of the layers coated on the reactor walls after an etching process in order to develop efficient cleaning processes of the plasma chamber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the SF 6 / O 2 plasma treatment in our experiment, SiO 2 and AlF are deposited from the chamber walls on the wafer piece. Cunge et al 9 showed that even in a SF 6 / O 2 plasma AlF can be released from the walls into the plasma and eventually deposit on the floating piece. The AlF 3 on the piece is thus not only coming from fluorination of the Al 2 O 3 piece and the piece really represents the actual chamber wall condition during the plasma treatment.…”
Section: A Deposition and Characterization Of Contaminants In The Plmentioning
confidence: 99%